Enough and as Good: A Formal Model of Lockean First Appropriation. Issue 3 (6th June 2018) - Kogelmann, Brian; Ogden, Benjamin G.
Abstract: In developing a theory of the first appropriation of natural resources from the state of nature, John Locke tells us that persons must leave "enough and as good" for others. Detailing exactly what this restriction requires divides right and left libertarians. Briefly, right libertarians interpret "enough and as good" as requiring no or very minimal restrictions on the first appropriation of natural resources, whereas left libertarians interpret "enough and as good" as requiring everyone to be entitled to an equal share of unappropriated resources, able to claim no more beyond this equal share. This article approaches the right versus left libertarian debate by developing a formal model that examines the welfare properties of different interpretations of the Lockean proviso. The model shows that underlying philosophical justifications for left libertarianism, when plausible assumptions hold, will actually be better served by a right libertarian proviso rather than a left libertarian one.